STRATEGY FOR IMPLEMENTING CATEGORIZATION ON MICRO SMALL AND MEDIUM ENTREPRISES AT JAKARTA ENTERPRENEUR PROGRAM IN THE PROVINCE OF JAKARTA - Reny Asmiyanti; Nurliah Nurdin; Firman Hadi Rivai (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to identify and formulate strategies that have not optimized the implementation of the Jakarta Entrepreneur Program Categorization for Micro, Small and Medium Enterprises (MSMEs) in the Special Region of Jakarta. In this study, based on Merilee S Grindle's policy implementation theory which includes the content of policy and context of implementation. This research method uses a descriptive and qualitative approach with data collection conducted by interviews and document review. In the analysis process using SWOT analysis as the main instrument in its preparation, then the next step to determine alternative strategic issues is used with the litmust test, with the most strategic issue obtained by strengthening the government's commitment to implementing MSME categorization in the jakpreneur program to improve the quality of MSME actors. From the results of this identification, several problems were found faced by the government and micro, small and medium enterprises (MSMEs) in improving the quality of MSMEs from beginner entrepreneurs to medium-sized entrepreneurs to established entrepreneurs.This research is important to identify the challenges and obstacles faced by MSME actors to be an important step in designing the right strategies and programs to improve the business conditions of MSME actors.